Drug war Mexico : politics, neoliberalism and violence in the new narcoeconomy - Watt, Peter (Educator) (Zed Books, 2012)
Mexico is in crisis. During the neoliberal era, narcotrafficking has flourished to become one of the country's biggest sources of revenue, as well as its most violent, with over 12,000 drug-related executions in 2011 alone. This insightful, controversial book throws new light on the situation, contending that the 'war on drugs' in Mexico is in fact a pretext for a US-backed strategy to bolster unpopular neoliberal policies, a weak yet authoritarian government and a radically unfair status quo.